2011
DOI: 10.1021/jo2012225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of siRNA Bases To Probe and Enhance RNA Interference

Abstract: Considerable attention has focused on the use of alternatives to the native ribose and phosphate backbone of small interfering RNAs for therapeutic applications of the RNA interference pathway. In this synopsis, we highlight the less common chemical modifications, namely those of the RNA nucleobases. Base modifications have the potential to lend insight into the mechanism of gene silencing and to lead to novel methods to overcome off-target effects that arise due to deleterious protein binding or mis-targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 65 publications
0
73
0
1
Order By: Relevance
“…Four major classes of chemical modifications (backbone, sugar, base, and terminal) have been developed to resist nuclease-catalyzed degradation of oligonucleotides and to improve siRNA stability in both fetal bovine and human serum (10)(11)(12)(13)(14)(15)26). To test the hypothesis that enzymatic hydrolysis of SNA-1 takes places at a site near the AuNP-facing terminus of the siRNA, thus leading to oligonucleotide fragments too short to remain hybridized and associated to SNA-1, we designed and analyzed SNA-1-(2′-H) 5 and SNA-1-(2′-OMe) 5 , where the RNA nucleotides of siRNA AR at positions 1-5 for both the senseand AS oligonucleotide (i.e., the AuNP-facing terminus) are substituted with 2′-H or 2′-OMe nucleotides and are therefore not susceptible to RNase-catalyzed hydrolysis (Fig.…”
Section: Degradation Of Sna-1 In Solutions Of Fbs Via Loss Of the Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Four major classes of chemical modifications (backbone, sugar, base, and terminal) have been developed to resist nuclease-catalyzed degradation of oligonucleotides and to improve siRNA stability in both fetal bovine and human serum (10)(11)(12)(13)(14)(15)26). To test the hypothesis that enzymatic hydrolysis of SNA-1 takes places at a site near the AuNP-facing terminus of the siRNA, thus leading to oligonucleotide fragments too short to remain hybridized and associated to SNA-1, we designed and analyzed SNA-1-(2′-H) 5 and SNA-1-(2′-OMe) 5 , where the RNA nucleotides of siRNA AR at positions 1-5 for both the senseand AS oligonucleotide (i.e., the AuNP-facing terminus) are substituted with 2′-H or 2′-OMe nucleotides and are therefore not susceptible to RNase-catalyzed hydrolysis (Fig.…”
Section: Degradation Of Sna-1 In Solutions Of Fbs Via Loss Of the Asmentioning
confidence: 99%
“…Chemically modified nucleotides [e.g., 2′-O-methyl (2′-OMe), 2′-deoxy-2′-fluoro (2′-F)] are commonly used to increase the stability of siRNA in serum-containing media (10)(11)(12)(13)(14)(15), and research efforts to develop therapeutic siRNA often use "design rules" and patterns for the placement of chemically modified nucleotides to enhance serum lifetimes. For example, multiple reports have shown that modifying all pyrimidines in the siRNA sequence with 2′-F modifications provides high serum stability without compromising activity (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…A thorough review of the chemical modifications is beyond the scope of this report but can be found elsewhere (Snove and Rossi, 2006;Peacock et al, 2011;Engels, 2013;Nolte et al, 2013). There are two common strategies, to reduce off-targeting -(I) Chemical modifications on the passenger strand preventing its loading, hence eliminating off-targeting caused by the passenger strand Snead et al, 2013) and (II) Chemical modifications in the seed region, which interfere with miRNA-like target recognition but do not prevent specific RNAi targeting.…”
Section: Mismatch Introductionmentioning
confidence: 99%
“…Several modifications were introduced. The thio (−SH), hydroxyl (−OH), or iodo (−I) can modify bases in specific sites or utilize the pseudouracil base in siRNA, which would augment potency of naked siRNA [31]. There are three most popular chemical modification sites on siRNA structure containing the phosphodiester backbone, ribose 2′-hydroxyl group (R-2′-OH), and ribose ring.…”
Section: Stabilizing the Sirna Deliverymentioning
confidence: 99%